Review of Empirical Research on Corporate Sustainability Practice: An Indonesian Context Towards SDG 12 - Elvia Ivada; Rahmawati Rahmawati; Djuminah Djuminah; Wahyu Widarjo (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To examine the implementation of corporate sustainability practices among Indonesian companies by reviewing empirical academic studies and identifying how the Triple Bottom Line (TBL) framework is adopted to address sustainability challenges. This study contributes to understanding responsible corporate practices and their relevance to achieving Sustainable Development Goal 12 (Responsible Consumption and Production). Method: A systematic literature review approach to analyze scholarly publications related to corporate sustainability practices in the Indonesian context. Following a systematic review protocol, 57 articles were selected and examined through content analysis using Atlas.ti software. The analysis focused on identifying sustainability practices based on the Triple Bottom Line framework, including economic, social, and environmental dimensions. Results: The findings indicate that most Indonesian sustainability studies utilize the TBL framework as the foundation for explaining corporate sustainability practices. However, sustainability implementation remains predominantly focused on reporting activities, while only a limited number of studies discuss the integration of TBL principles into business operations, organizational strategies, and corporate culture. Novelty: The study provides a comprehensive review of corporate sustainability practices in Indonesia by identifying the gap between sustainability reporting and strategic implementation. The findings emphasize the importance of embedding sustainability principles into corporate decision-making and operational processes to strengthen responsible production practices and support SDG 12 achievement.